Students’ Motivation, Challenges, and Results in TOEFL Learning Process Through Online Preparation Course - Amalia, Widya; Rudi Hartono; Hendi Pratama (English Education Journal, 2024)
Online TOEFL preparation course has been very popular as it brings accessibility and flexibility to students. However, the effectiveness of these TOEFL preparation can be affected by some factors, namely students’ motivation, challenges they faced in learning TOEFL online, and the score improvements in their overall TOEFL score. This research aims at evaluating students’ motivation in participating in online TOEFL preparation course, evaluating what challenges students in the process of learning virtually, and evaluating the extent to which students’ score improve after they have completed 6-hour online preparation course. This research emploes explanatory sequential mixed-method design. The instruments utilized are questionnaire, interview, and pre-test and post-test. The result of this research highlights the students’ motivation and challenges in learning TOEFL online and the extent to which their TOEFL scores improve. This study is hoped to add reference for future researchers to explore more about TOEFL preparation for wider participants and longer duration of preparation.